The first domestication : how wolves and humans coevolved - Pierotti, Raymond John; Fogg, Brandy R. (Yale University Press, 2017)
"A riveting look at how dog and humans became best friends, and the first history of dog domestication to include insights from Indigenous peoples In this fascinating book, Raymond Pierotti and Brandy Fogg change the narrative about how wolves became dogs and in turn, humanity's best friend. Rather than describe how people mastered and tamed an aggressive, dangerous species, the authors describe coevolution and mutualism. Wolves, particularly ones shunned by their packs, most likely initiated the relationship with Paleolithic humans, forming bonds built on mutually recognized skills and emotional capacity. This interdisciplinary study draws on sources from evolutionary biology as well as tribal and Indigenous histories to produce an intelligent, insightful, and often unexpected story of cooperative hunting, wolves protecting camps, and wolf-human companionship. This fascinating assessment is a must-read for anyone interested in human evolution, ecology, animal behavior, anthropology, and the history of canine domestication."--Provided by publisher